Innovative Approaches to Developing Aesthetic and Creative Competencies in Fine Arts Education - Sayfiyeva Ozoda Madamin qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This article investigates innovative approaches for developing students’ aesthetic and creative competencies in fine arts education. It focuses on the use of interactive lessons, project-based activities, and digital tools to enhance visual perception, artistic interpretation, and creative expression. The study emphasizes the importance of student-centered pedagogy and a supportive learning environment in promoting both aesthetic awareness and creativity among learners.